Rancang Bangun Sistem Aplikasi Packaging Labeling Berbasis Web - Nur Azizah; Vinsensius Yalasena Adi Nugroho; Edi Siswanto (UNIVERSITAS RAHARJA, 2020)
The development of technology in the computer-based digital era is currently considered to be developing very rapidly. PT.Pratama Abadi Industri a company engaged in the manufacture of shoes with a fairly well-known brand in Indonesia. In carrying out the packaging labeling data reporting, it still uses office-based applications namely Microsoft Word and Microsoft Excel, which results in suboptimal performance results. Then a web-based packing labeling application system was built. In determining research and research design requires a method to see the development of the design and research, the methods applied include the SDLC method in the form of a waterfall, where a website system that has been designed with PHP Framework Codeigniter as a programming language and SQL as database storage. To design a packaging labeling application system using the Unified Modeling Language (UML) as a modeling tool consisting of Use Case Diagrams, Sequence Diagrams, and Activity Diagrams. The results of the web-based packaging application system are expected to provide solutions to the problems encountered